Sustainable operation? Measuring the actual consumption of a hybrid car and determining its consumption curve - ZSOMBOKImre (Cognitive Sustainability, 2023)
Sustainability is one of the most commonly used terms concerning renewable energy, environmental protection and energy management. Without a doubt, understanding its full meaning, it is clear that sustainability is paramount for the quality of life of future generations and for the Earth as a living space. The presented work aims to give an overview of the importance of on-board management in hybrid vehicles as an important tool to increase their contribution to sustainable mobility. Real-world condition measurements were carried out based on the available cognitive features of an average vehicle. Several main consumers were also tested to present their role within cognitive and sustainable mobility. Results show that there is a function between the battery load level and the hybrid vehicle electric power use likeliness. Among the primary but under-addressed concerns today are the uninhibited exploitation of non-renewable energy sources and the avoidance of pollution.